FACTORS AFFECTING PURCHASE INTENTION TOWARDS NATURAL SKIN CARE PRODUCT - Yati, Putri Nuzulil; Wisesa, Anggara (Journal of Business and Management, 2018)
Abstract. Indonesia is home to hundreds of run-small business in cosmetics producers that concerns in producing natural skin care products (Global Business Guide Indonesia, 2014), but the tendency of choosing import brands still tend to be high, although some of them begin to look at local brands whereas Indonesia government continues to strive to increase Peningkatan Penggunaan Produk Dalam Negeri (P3DN). There are several independent variables include in this research; Consumer Values (Health, Environment, Apperance Consciousness), Attitudes toward Natural Skin Care Product, Product Stimulus, Price Stimulus, Promotion Stimulus, and Place Stimulus. This study has limitations in terms of availability of data about the total population of skin care natural users in Indonesia or any areas of Indonesia. Therefore, The Author uses judgement sampling technique as a reference in selecting samples, which had already collected 446 samples, who has experience consuming at least one natural skin care product before. To gain the result to know whether there is significant affect among each independent variables toward dependent variables the, The Author use Multiple Linear Regression with SPSS tool. The result shows that there are positive relation between all independent variables with purchase intention toward natural skin care product, except for Attitudes toward Price. Better product will encourage consumers’ purchase intention, so people are careless with the price provided that there are better product that will satisfy themselves.Keywords: Attitudes, Consumer Values, Marketing Mix, Natural Skin Care Product, Purchase Intention